Baptism or Gospel of Grace?: Romans 6 Revisited - Kwon, Youngju (The expository times, 2017)
Romans 6 has been a difficult chapter owing to a number of dialectical elements: being and doing, theology and ethics, indicative and imperative, divine and human agency, and ‘already’ and ‘not yet’. Despite some previous attempts to view this chapter as presenting the theology of baptism, this article argues that Paul’s primary concern in this chapter is to explain the fundamentals of the gospel of grace and their implications for Christian life. The proper understanding of the gospel of grace includes: that everyone belongs to one of the two domains of authority (either under the domain of law/sin or under the domain of grace/Christ); that by the grace of God believers have experienced the transfer of lordship; and that despite this transfer, both aspects of ‘already’ and ‘not yet’ are creatively working together in Christian life. This article concludes with two implications: that the gospel of grace does require (rather than ignore) a moral life and that in Christian moral life we must not lose sight of both God’s empowerment and humans’ power.